Fetal red blood cell hematology at mid-pregnancy among fetuses at risk of homozygous β-thalassemia disease - Kasemsri Srisupundit (2018)
Objective: To compare red blood cell hematology among fetuses at risk of homozygous β-thalassemia disease at mid-pregnancy. Materials and Methods: Eighty-six fetuses, 18 to 22 gestational weeks, at risk of homozygous β-thalassemia disease undergoing cordocentesis between December 2010 and June 2012 were recruited in the study. Red blood cell parameters were measured and final diagnosis of thalassemia status was based on fetal hemoglobin typing by high performance liquid chromatography technique and DNA analysis. The fetuses were categorized into 3 groups as normal β-globin genotype, β-thalassemia trait, and homozygous β-thalassemia disease. Results: Mean maternal age and mean gestational age were 26.56 ± 6.36 and 19.12 ± 1.06 weeks, respectively. The prevalence of fetuses with homozygous β-thalassemia disease, β-thalassemia trait, and normal β-globin genotype fetuses were 29.07% (25 cases), 20.93% (18 cases), and 50% (43 cases), respectively. All of red blood cell parameters were not significantly different among the 3 groups of fetuses. No affected fetus had anemia during midpregnancy. Conclusion: No significant difference in red blood cell parameters among unaffected and affected fetuses with homozygous β-thalassemia disease was found. Copyright © 2013 by Lippincott Williams & Wilkins.